2009
DOI: 10.1016/j.ydbio.2009.02.026
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of development of ionocytes rich in vacuolar-type H+-ATPase in the skin of zebrafish larvae

Abstract: Mitochondrion-rich cells (MRCs), or ionocytes, play a central role in aquatic species, maintaining body fluid ionic homeostasis by actively taking up or excreting ions. Since their first description in 1932 in eel gills, extensive morphological and physiological analyses have yielded important insights into ionocyte structure and function, but understanding the developmental pathway specifying these cells remains an ongoing challenge. We previously succeeded in identifying a key transcription factor, Foxi3a, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
68
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 38 publications
6
68
0
Order By: Relevance
“…Hsiao et al (2007) first proposed a regulatory pathway for ionocyte differentiation and specification in zebrafish, and this model was mostly supported and further explored in subsequent studies (Fig. 2) (Janicke et al, 2007;Esaki et al, 2009;Hwang and Perry, 2010;Hwang et al, 2011). Janicke et al (2007) proved that ionocytes are derived from nonneural ectoderm via lineage tracing experiments.…”
Section: Specification and Differentiation Of Epidermal Cellsmentioning
confidence: 89%
“…Hsiao et al (2007) first proposed a regulatory pathway for ionocyte differentiation and specification in zebrafish, and this model was mostly supported and further explored in subsequent studies (Fig. 2) (Janicke et al, 2007;Esaki et al, 2009;Hwang and Perry, 2010;Hwang et al, 2011). Janicke et al (2007) proved that ionocytes are derived from nonneural ectoderm via lineage tracing experiments.…”
Section: Specification and Differentiation Of Epidermal Cellsmentioning
confidence: 89%
“…HRCs and NaRCs). Cruz et al (Cruz et al, 2013) demonstrated that cortisol treatment increased the proliferation of NaRCs and HRCs in zebrafish larval skin and adult gill through its stimulatory effects on foxi3a/3b, transcription factors involved in the regulation of ionocyte differentiation Esaki et al, 2009;Hsiao et al, 2007;Jänicke et al, 2007). Because of the increase in wholebody cortisol levels in acid-exposed larvae, the role of cortisol in ionocyte proliferation/epidermal development offers an attractive mechanism to explain the observed increase in HRCs in response to acid exposure.…”
Section: The Journal Of Experimental Biologymentioning
confidence: 99%
“…Thus, zebrafish embryos likely express the toxin's receptor GM1, and it can bind CT. We also performed confocal microscopy on live embryos exposed to fluorophore-labeled CTB and localized the bulk of toxin uptake to surface epithelial mitochondrion-rich cells (MRCs), the depletion of which correlated with toxin resistance (Supplemental Figure 2 and Supplemental Video 1). It is of note that these cells regulate salt and water homeostasis in the embryo (34); however, intoxication of other cell types might contribute to the overall phenotype observed (see below).…”
Section: Ct Intoxicates Zebrafish By Binding Gm1 and Crossing The Er mentioning
confidence: 99%
“…Embryos (40-hpf) were incubated in embryo water containing 20 nm CTB-Alexa Fluor 488 for 50 minutes, and then a further 10 minutes with 1 μM MitoTracker (labels MRCs), thought to regulate salt and water homeostasis in the zebrafish embryo (34). Embryos were washed and anesthetized (50 μg/ml MS-222) prior to imaging.…”
Section: Reagents and Antibodies Vibrio Cholerae Ct And Ctb Were Purmentioning
confidence: 99%